2022
DOI: 10.1128/mbio.02421-22
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Severe Acute Respiratory Syndrome Coronavirus 2 Variants in the Ferret Model

Abstract: Continued surveillance and risk assessment of emerging SARS-CoV-2 variants are critical for pandemic response and preparedness. As such, in vivo evaluations are indispensable for early detection of variants with enhanced virulence and transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 68 publications
(78 reference statements)
6
29
0
Order By: Relevance
“…WA/1 and Delta SCOV2 strains were previously shown to transmit efficiently in a ferret DCT model following i.n. inoculation ( 26 ); comparable transmissibility with the two viruses was detected following o.c. inoculation, despite a 1- to 2-day delay in infectious virus detection in contact animals relative to donor animals inoculated intranasally ( Fig.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…WA/1 and Delta SCOV2 strains were previously shown to transmit efficiently in a ferret DCT model following i.n. inoculation ( 26 ); comparable transmissibility with the two viruses was detected following o.c. inoculation, despite a 1- to 2-day delay in infectious virus detection in contact animals relative to donor animals inoculated intranasally ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…We recently found that SCOV2 RNA could be detected sporadically in ferret CW specimens following i.n. inoculation ( 26 ), but the capacity of SCOV2 to cause infection following ocular exposure in ferrets was not known. Employing the same experimental design as described above, ferrets were inoculated by the o.c.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations